Development and evaluation of a training program for interpreters in the field of trauma-focused cognitive behavioral therapy - Müller, Lauritz Rudolf Floribert; Herold, Monja Lucia; Unterhitzenberger, Johanna; Rosner, Rita (Frontiers in Psychology, 2023)
Background The treatment of traumatized refugee minors is often challenging because of language barriers. International guidelines, therefore, recommend the use of language mediators. However, there is a scarcity of evaluated training programs that prepare language mediators to translate during psychotherapy developed specifically for this patient group, for instance trauma-focused cognitive behavioral therapy (TF-CBT). Methods Based on an extensive literature review and in collaboration with an expert focus group, a one-day TF-CBT-specific online training program was developed for language mediators willing to work with minor refugees, and delivered on nine occasions between November 2020 and June 2021. The participants answered pre- and post-training questions about trauma- and TF-CBT-related knowledge and attitudes relevant to therapy, as well as the perceived usefulness of the training. Bayesian estimation was used to determine pre-post changes. Results A total of 129 participants speaking 35 different languages participated in the training program. Analyses revealed 95% highest density intervals not containing the null with respect to knowledge gain (effect size median 0.28) and change in treatment-appropriate attitudes (effect size median 0.31). The participants rated the training as useful. Conclusion The TF-CBT-specific training course was successfully carried out. It was likely to disseminate both knowledge gains and a shift toward more treatment-appropriate attitudes. It was perceived as useful by the participants. Given the scarcity of evaluated training programs for language mediators working with minor refugees, the results are promising. The limitations include the lack of both a control group and the verification of the results using an external outcome measure.